Analisis Kesalahan Berbahasa dalam Bidang Semantik pada Cerpen “Gie” Karya Egha De Latoya (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to analyze semantic language errors found in the short story "Gie" by Egha De Latoya. The analysis focuses on the forms of meaning errors that include ambiguity, inappropriate word usage, redundancy, and unclear context that appear in the short story text. This study uses a qualitative descriptive method with a documentation study as a data collection technique. Data analysis was carried out through several stages, namely data identification, classification of types of semantic errors, and description of errors based on applicable Indonesian language rules. The results of the study indicate that in the short story "Gie" there are still a number of semantic errors. These errors include ambiguity of meaning due to the use of inappropriate metaphorical diction, word choice that creates double meanings, and redundancy that causes waste of meaning and reduces the effectiveness of sentences. In addition, unclear context was also found that can affect the reader's understanding of the story's content. Factors causing these semantic errors include a lack of understanding of the context of meaning and the influence of the use of everyday language in writing short stories. The findings of this study are expected to be evaluation materials for short story writers so that the use of language is more precise, clear, and effective in conveying messages to readers.